Biphasic Porous Structures formed by Monomer/Water Interface Stabilization with Colloidal Nanoparticles. Issue 21 (8th October 2021) - Pizzetti, Fabio; Rossetti, Arianna; Marchetti, Alessandro; Castiglione, Franca; Vanoli, Valeria; Coste, Elena; Veneruso, Valeria; Veglianese, Pietro; Sacchetti, Alessandro; Cingolani, Alberto; Rossi, Filippo
Abstract: Bicontinuous jammed emulsions (known as bijels) are Pickering emulsions where oil and water are both continuous phases. These interconnected structures, stabilized by colloidal nanoparticles at the oil–water interface, have been used in a wide range of applications. Among these, catalysis and encapsulation of solutes has showed promising potential, but the low mechanical properties of the systems limit their use. Here it is proposed that the use of a hydrophobic monomer able to polymerize in bulk and form a biphasic porous structure with polymer and water as immiscible phases. The final system is stabilized by colloidal nanoparticles made of hydroxyapatite, and the system's ability to release both hydrophilic and hydrophobic drugs has been demonstrated. The strategy has been proven to be highly versatile and may be tuned with a diversity of monomers and nanoparticles to satisfy specific industrial and medical needs. Abstract : For the first time, biphasic porous structures consisting of monomer (hydrophobic, that can polymerize in bulk condition) and water can be formed simply by mixing the system using colloid nanoparticles without the typical presence of surfactants. The produced system exhibits high stability at body temperature and promising performances for multidrug delivery approach.